THEORETICAL AND PRACTICAL DILEMMAS OF DEFINING THE CONCEPT OF INNOVATION - Myjak, Teresa (Management and Administration Journal, 2024)
Innovations can take the form of implementing a modernised process, method or practical solutions in an enterprise, aimed at achieving specific benefits in the economic and social sphere. Innovations are related to specific changes in various functional areas of the organisation, including personnel. The cognitive purpose of the publication is to present the concept of innovation based on selected – national and foreign – literature on the subject. The goal of the research was to identify how innovations are defined in economic practice, especially in relation to the personnel area. The research problem was focused on obtaining an answer to the question regarding the perception of the concept of innovation in the personnel area. It was assumed that innovation in the personnel area is understood as the implementation of an improved process, method or solutions in the enactment of the personnel function. The empirical data was obtained using a survey technique with the use of a questionnaire. Empirical research was characterised by: subject, object, time and research space. The most important findings indicate that almost half of the respondents perceive innovation as a process, method or solution in the implementation of the personnel function. The conclusions from the research boil down to the statement that the Schumpeterian concept (promoting the understanding of innovation as the first application of a given invention in economy) turned out to be a rather distant concept for contemporary practitioners.